IMPORTANT TOOLS AND METHODS OF STREAMING FOREIGN LANGUAGES - Miyassar Akhmedova (Web of Journals Publishing, 2025)
This article is devoted to modern methods and approaches to teaching a foreign language, their impact on the learning process and the results of students. The article analyzed and examined the result of the development of a communicative approach, integration of modern technologies, competence of individual styles and intercultural communication in foreign language lessons. The enrichment of the educational process through modern technologies, including technical means, and the development of information technical competence in students, as well as language skills in teaching foreign (English) language, made it possible to stimulate them through analyzes. In the successful preparation of students, modern methods have proven to be relevant in the educational environment.
Keywords: Foreign language, modern methods, communicative approach, technologies in education, individualization of learning, intercultural, communication, competence, teaching of foreign languages.